A longitudinal study of the mechanical properties of injured brain tissue in a mouse model. (July 2017) - Feng, Yuan; Gao, Yuan; Wang, Tao; Tao, Luyang; Qiu, Suhao; Zhao, Xuefeng
Abstract: Mechanical properties of brain tissue are crucial to understand the mechanism of traumatic brain injury (TBI). Over the past several decades, most of the studies focused on healthy brain tissues, while few of them are about the injured tissues. Therefore, limited knowledge is known about the mechanical properties of the injured brain tissues. In this study, we used an in vivo mouse model with a weight drop device to study injured brain tissues. Around the injury site, mechanical properties of the injured, neighboring, and the corresponding contralateral regions of interest (ROIs) were measured over five temporal points by indentation. Longitudinal and regional comparisons of the mechanical properties revealed that the ROI of the injured tissue had a higher elastic modulus than the contralateral counterpart one-hour post-injury. However, the elastic modulus decreased one-day post-injury and recovered to be close to the contralateral ROI in 7 days. The elastic modulus curves of the injured and the contralateral counterpart ROIs crossed at time points of 12 h and 1 day post-injury, where two significant increases of glial fibrillary acidic protein (GFAP) positive cells were observed. Biological staining results indicated that both the astrocytic responses and the morphological structure could affect the mechanical properties of the injured tissue. The observed longitudinal changes of the mechanical properties at the tissue level and the morphological and biological changes at the cellular level provide insights into understanding the mechanism of TBI. Results are also meaningful for applying emerging in vivo diagnostic tools such as magnetic resonance elastography (MRE) in TBI detection.